Diabetic foot ulcer classification using an enhanced coordinate attention integrated ConvNext model - L. Jani Anbarasi; R Neeraja; S. Geetha; R. Vidhya; Vinayakumar Ravi; D Dhanya (Physical and Engineering Sciences in Medicine, 2026)

Seismic fragility assessment of reinforced concrete bridges: a comprehensive review of methodologies, isolators, and soil structure interaction - Ashwini Satyanarayana; Dushyanth V. Babu R; H. M. Sheethal; L. Geetha (Innovative Infrastructure Solutions, 2026)

Novel bacteriophages effectively target multidrug-resistant clinical isolates of Klebsiella pneumoniae - Malavika Binitha Hari; A. L. Sreelekshmi; Pradeesh Babu; Abhijith Pulimoottil Jaykumar; Sivaraj Barath; Sharayu Magar; Sutharsan Govindarajan; John Bernet Johnson; Anil Kumar; Jayalekshmi Haripriyan; Victor Nizet; Jason Gill; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Preparation and characterization of activated carbon from corn cob by chemical activation and their adsorption of brilliant green dye from wastewater - Sakthivel Kumaravel; M. Geetha; Theophile Niyitanga; D. Senthil Kumar; Mysoon M. Al-Ansari; R. Mythili; Sanjeevamuthu Suganthi; L. Guganathan; A. Murugan; S. Ragupathy (Process Safety and Environmental Protection, 2024)

Revealing Adaptability of Sugar Beet (Beta vulgaris) Genotypes Through Environmental Interaction (GEI) connecting Variations in Tuber Yield - M. Shanmuganathan; D. Kumaresan; S. Geetha; M. Dhasarathan; M. Jayaramachandran; R. Sudhagar; T. Selvakumar; L. Chitra; S. Mohan; A. Gurusamy; K. Iyanar (Agricultural Research, 2023)

Comparison of multi-influence factor, weight of evidence and frequency ratio techniques to evaluate groundwater potential zones of basaltic aquifer systems - Nitin L. Rane; Geetha K. Jayaraj (Environment, Development and Sustainability, 2022)

Additive main effects and multiplicative interaction analyses of yield performance in rice genotypes for general and specific adaptation to salt stress in locations in India - S. L. Krishnamurthy; P. C. Sharma; D. K. Sharma; Y. P. Singh; V. K. Mishra; D. Burman; B. Maji; S. Mandal; S. K. Sarangi; R. K. Gautam; P. K. Singh; K. K. Manohara; et al. (Euphytica, 2021)
The aim of this study was to identify stable rice genotypes tolerant to a salt stress environment and to identify ideal mega-environments using AMMI (additive main effects and multiplicative interaction) stability model analysis. A total of 13 rice genotypes and three salt tolerance checks were evaluated across 13 salt stress locations (alkaline and saline) for the two kharif seasons of 2014 and 2015. Genotype CSR 36 (CHK3) was found to be the most ideal of those tested. Genotypes CHK2 (CST 27) and IR 87952-1-1-1-2-3-B (G05) were found to be the most stable, with above average yields. The check CSR 36 (CHK3) genotype was the best performer in the majority of the environments studied, followed by CSR 27 (CHK2) and IR 87952-1-1-1-2-3-B (G05) which were the best genotypes in the mega-environment consisting of 21 environments evaluated across stress locations and year combinations. Overall, the most promising genotype (IR 87952-1-1-1-2-3-B) had high mean yield and stability and could be used for commercial cultivation or used as donor for breeding programs across salt-affected soils. The genotypes GN13 (IR 87938-1-1-2-1-3-B) and GN11 (IR 87938-1-2-2-1-3-B) showed 60–80% yield advantage at specific salt stress locations, showing that these genotypes could be used for specific environments of salt-affected soils in India.

Albumin nanoparticles coated with polysorbate 80 for the targeted delivery of antiepileptic drug levetiracetam into the brain - Barnabas Wilson; Janani Selvam; Geetha K. Mukundan; Kudumula B. Premakumari; Josephine L. Jenita (Drug Delivery and Translational Research, 2020)

Enhanced anti-fibrogenic effects of novel oridonin derivative CYD0692 in hepatic stellate cells - Fredrick J. Bohanon; Xiaofu Wang; Brittany M. Graham; Anesh Prasai; Sadhashiva J. Vasudevan; Chunyong Ding; Ye Ding; Geetha L. Radhakrishnan; Cristiana Rastellini; Jia Zhou; Ravi S. Radhakrishnan (Molecular and Cellular Biochemistry, 2015)

MHC class II‐assortative mate choice in European badgers ( Meles meles ) - Yung Wa Sin; Geetha Annavi; Chris Newman; Christina Buesching; Terry Burke; David W. Macdonald; Hannah L. Dugdale (Molecular Ecology, 2015)
The major histocompatibility complex ( MHC ) plays a crucial role in the immune system, and in some species, it is a target by which individuals choose mates to optimize the fitness of their offspring, potentially mediated by olfactory cues. Under the genetic compatibility hypothesis, individuals are predicted to choose mates with compatible MHC alleles, to increase the fitness of their offspring. Studies of MHC ‐based mate choice in wild mammals are under‐represented currently, and few investigate more than one class of MHC genes. We investigated mate choice based on the compatibility of MHC class I and II genes in a wild population of European badgers ( Meles meles ). We also investigated mate choice based on microsatellite‐derived pairwise relatedness, to attempt to distinguish MHC ‐specific effects from genomewide effects. We found MHC ‐assortative mating, based on MHC class II , but not class I genes. Parent pairs had smaller MHC class II DRB amino acid distances and smaller functional distances than expected from random pairings. When we separated the analyses into within‐group and neighbouring‐group parent pairs, only neighbouring‐group pairs showed MHC ‐assortative mating, due to similarity at MHC class II loci. Our randomizations showed no evidence of genomewide‐based inbreeding, based on 35 microsatellite loci; MHC class II similarity was therefore the apparent target of mate choice. We propose that MHC ‐assortative mate choice may be a local adaptation to endemic pathogens, and this assortative mate choice may have contributed to the low MHC genetic diversity in this population.

A maize α-zein promoter drives an endosperm-specific expression of transgene in rice - J. Beslin Joshi; S. Geetha; Birla Singh; K. K. Kumar; E. Kokiladevi; L. Arul; P. Balasubramanian; D. Sudhakar (Physiology and Molecular Biology of Plants, 2015)

Pathogen burden, co‐infection and major histocompatibility complex variability in the E uropean badger ( M eles meles ) - Yung Wa Sin; Geetha Annavi; Hannah L. Dugdale; Chris Newman; Terry Burke; David W. MacDonald (Molecular Ecology, 2014)
Pathogen‐mediated selection is thought to maintain the extreme diversity in the major histocompatibility complex ( MHC ) genes, operating through the heterozygote advantage, rare‐allele advantage and fluctuating selection mechanisms. Heterozygote advantage (i.e. recognizing and binding a wider range of antigens than homozygotes) is expected to be more detectable when multiple pathogens are considered simultaneously. Here, we test whether MHC diversity in a wild population of European badgers ( M eles meles ) is driven by pathogen‐mediated selection. We examined individual prevalence (infected or not), infection intensity and co‐infection of 13 pathogens from a range of taxa and examined their relationships with MHC class I and class II variability. This population has a variable, but relatively low, number of MHC alleles and is infected by a variety of naturally occurring pathogens, making it very suitable for the investigation of MHC –pathogen relationships. We found associations between pathogen infections and specific MHC haplotypes and alleles. Co‐infection status was not correlated with MHC heterozygosity, but there was evidence of heterozygote advantage against individual pathogen infections. This suggests that rare‐allele advantages and/or fluctuating selection, and heterozygote advantage are probably the selective forces shaping MHC diversity in this species. We show stronger evidence for MHC associations with infection intensity than for prevalence and conclude that examining both pathogen prevalence and infection intensity is important. Moreover, examination of a large number and diversity of pathogens, and both MHC class I and II genes (which have different functions), provide an improved understanding of the mechanisms driving MHC diversity.

Genetic epidemiology of cardiometabolic risk factors and their clustering patterns in Mexican American children and adolescents: the SAFARI Study - Sharon P. Fowler; Sobha Puppala; Rector Arya; Geetha Chittoor; Vidya S. Farook; Jennifer Schneider; Roy G. Resendez; Ram Prasad Upadhayay; Jane VandeBerg; Kelly J. Hunt; Benjamin Bradshaw; Eugenio Cersosimo; et al. (Human Genetics, 2013)

Temporal Trends of Malondialdehyde in Stored Human Plasma - Arun Kumar; B. S. Dhillon; D. N. Rao; Geetha Menon; Hari Shankar; L. K. Dhaliwal; Maiti Leema; Nomita Chandhiok; Neeta Kumar; Rohini Sehgal; Suneeta Mittal; Sumitu Sahdev; et al. (Indian Journal of Clinical Biochemistry, 2012)

Characterisation of twenty-one European badger (Meles meles) microsatellite loci facilitates the discrimination of second-order relatives - Geetha Annavi; Deborah A. Dawson; Gavin J. Horsburgh; Carolyn Greig; Hannah L. Dugdale; Chris Newman; David W. Macdonald; Terry Burke (Conservation Genetics Resources, 2011)

Identification and partial characterization of soluble and membrane-bound KDN(deaminoneuraminic acid)-glycoproteins in human ovarian teratocarcinoma PA-1, and enhanced expression of free and bound KDN in cells cultured in mannose-rich media - Sadako Inoue; Geetha L. Poongodi; Nimmagadda Suresh; Tschining Chang; Yasuo Inoue (Glycoconjugate Journal, 2006)

Extension of Rapid Phase-Contrast Magnetic Resonance Imaging Using BRISK in Multidirectional Flow - Bradley L. Hershey; Mark Doyle; Eduardo Kortright; Rohan More; Geetha Rayarao; Andreas Anayiotos (Annals of Biomedical Engineering, 2005)

A small molecule antagonist of the α v β3 integrin suppresses MDA-MB-435 skeletal metastasis - John F. Harms; Danny R. Welch; Rajeev S. Samant; Lalita A. Shevde; Mary E. Miele; Geetha R. Babu; Steven F. Goldberg; Virginia R. Gilman; Donna M. Sosnowski; Dianalee A. Campo; Carol V. Gay; Lynn R. Budgeon; et al. (Clinical & Experimental Metastasis, 2004)

Rhythm and soul in the avian pineal - Arjun Natesan; L. Geetha; Martin Zatz (Cell and Tissue Research, 2002)

Safety profile of ibuprofen suspension in young children - E. Ashraf; L. Ford; R. Geetha; S. Cooper (Inflammopharmacology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Separation of bovine heart galactose lectin from endogenous glycoproteins co-purified with the lectin during affinity chromatography - P. S. Appukuttan; K. I. Annamma; M. Geetha; P. L. Jaison (Journal of Biosciences, 1998)